2020
DOI: 10.1139/cgj-2019-0547
|View full text |Cite
|
Sign up to set email alerts
|

Influence of phase difference between kinematic and inertial loads on seismic behaviour of pile foundations in layered soils

Abstract: A series of dynamic centrifuge experiments was conducted on model pile foundations embedded in a two-layered soil profile consisted of soft-clay layer underlain by dense sand. These experiments were specifically designed to investigate the individual effect of kinematic and inertial loads on a single pile and a 3×1 row pile group during model earthquakes. It was observed that the ratio of free-field soil natural frequency to the natural frequency of structure might not govern the phase relationship between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This is due to the phase difference between the kinematic and inertial loads. For the same tested pile foundations, Garala and Madabhushi [18] has shown that there is a significant phase difference between the kinematic and inertial loads for the single pile during BE2, BE4 and BE5 excitations and hence the pile accelerations in K+I flight are smaller than those in K flight. For all other cases, the kinematic and inertial loads act together or with smaller phase difference, leading to larger pile accelerations in K+I flight compared to K flight.…”
Section: Acceleration Response Of Soil Strata and Pile Foundationsmentioning
confidence: 92%
See 4 more Smart Citations
“…This is due to the phase difference between the kinematic and inertial loads. For the same tested pile foundations, Garala and Madabhushi [18] has shown that there is a significant phase difference between the kinematic and inertial loads for the single pile during BE2, BE4 and BE5 excitations and hence the pile accelerations in K+I flight are smaller than those in K flight. For all other cases, the kinematic and inertial loads act together or with smaller phase difference, leading to larger pile accelerations in K+I flight compared to K flight.…”
Section: Acceleration Response Of Soil Strata and Pile Foundationsmentioning
confidence: 92%
“…An air hammer device, a small actuator that can act as a source to induce waves within the soil model [17], was placed Published in Soil Dynamics and Earthquake Engineering 153 2022 107110 at the bottom of the model on a 10-15 mm thick sand layer during sand pouring. The detailed model preparation procedure and equivalent prototype characteristics of a single pile can be found in Garala [16] and Garala and Madabhushi [18]. The unit weight of the saturated clay and the sand is 16.2 kN/m 3 and 20.4 kN/m 3 , respectively.…”
Section: Centrifuge Tests Descriptionmentioning
confidence: 99%
See 3 more Smart Citations